2016
DOI: 10.21548/32-2-1376
|View full text |Cite
|
Sign up to set email alerts
|

Ampelographic and Molecular Characterisation of Aglianico Accessions (Vitis vinifera L.) Collected in Southern Italy

Abstract: To characterise 31 different Aglianico accessions randomly collected in Southern Italy, 30 ampelographic descriptors, 13 SSRs and 10 AFLP primer combinations were analysed. An appreciable variation of ampelographic descriptors was revealed mainly by mature leaf traits, while very few variations were recorded for shoot and berry traits. Similarly, all SSR loci revealed molecular monomorphism and AFLPs with a very high genetic similarity (Dice coefficient) among all the accessions considered. One of the aims of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
8
1
1
Order By: Relevance
“…No relationship between polymorphic SNP loci and biotypes was detected, and the low number of polymorphic loci (four) could be related to more unreliable results than to genetic intra‐varietal variability. The genetic uniformity of Aglianico biotypes based on SNP profiles corroborated the results obtained with a small number of molecular markers (Costantini et al , Alba et al , De Lorenzis et al ). Nevertheless, a recent investigation on the VvMybA1 and VvMybA2 genes of Aglianico biotypes, involved in the biosynthetic pathway of anthocyanins (Boss et al , Kobayashi et al ), revealed allelic polymorphisms among biotypes, regarding the detection of functional and non‐functional alleles for both genes (De Lorenzis et al ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…No relationship between polymorphic SNP loci and biotypes was detected, and the low number of polymorphic loci (four) could be related to more unreliable results than to genetic intra‐varietal variability. The genetic uniformity of Aglianico biotypes based on SNP profiles corroborated the results obtained with a small number of molecular markers (Costantini et al , Alba et al , De Lorenzis et al ). Nevertheless, a recent investigation on the VvMybA1 and VvMybA2 genes of Aglianico biotypes, involved in the biosynthetic pathway of anthocyanins (Boss et al , Kobayashi et al ), revealed allelic polymorphisms among biotypes, regarding the detection of functional and non‐functional alleles for both genes (De Lorenzis et al ).…”
Section: Discussionsupporting
confidence: 78%
“…Based on the Moio () results, Vulture had a high concentration of anthocyanins and a low concentration of phenolic substances both in skins and seeds, Taburno had the lowest concentration of anthocyanins, but the highest concentration of phenolic substances in seeds and Taurasi had an average concentration of these components. Moreover, the monophyletic origin of these biotypes was confirmed by DNA fingerprinting (Costantini et al , Alba et al , De Lorenzis et al ); however, the amplification of microsatellite (SSR) markers did not reveal differences in the allelic profile of Aglianico biotypes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Confirmation occurs in the indirect relationship of Pinot Noir with Aglianico [36,37]. Both, they are well connected to their lands through progenies not yet identified.…”
Section: The Case Of Pinot Syrah and Aglianicomentioning
confidence: 88%
“…Vegetative propagation is commonly used for grapevine (Vitis vinifera L.) and this asexual propagation method ensures that the plants are genetically identical copies. Anyway, during this process, spontaneous somatic mutations could create new allelic variants in plants, which could yield to phenotypes different in some traits with respect to the original mother plant [2]. Ampelography and secondary metabolites profiles have proven to be the best tools for the characterisation of the intra-varietal variability of grapevine germplasm [3].…”
Section: Introductionmentioning
confidence: 99%